The Advantages of Using a Modern Presentation Program to Prepare a Presentation - Makhkamova Dilshodakhon Khabibjon qizi (Zien Journals, 2022)
This article provides recommendations for students and teachers to prepare their work (independent work, project work, presentation, etc.) using modern presentation software. The article gives a brief overview of the possibilities and advantages of several new programs over other programs.
Keywords: presentation; text; drawing; slide